2016
DOI: 10.1021/acsami.6b08808
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electrostimulated Drug Delivery System Based on PLLA Composites Exploiting the Multiple Functions of Graphite Nanoplatelets

Abstract: A novel drug delivery system based on poly(l-lactide) (PLLA), graphite, and porphyrin was developed. In particular, 5,10,15,20-tetrakis(4-hydroxyphenyl)porphyrin (THPP) was chosen because, besides its potential as codispersing agent of graphite, it is a pharmacologically active molecule. Graphite nanoplatelets, homogeneously dispersed in both the neat PLLA and the PLLA/porphyrin films, which were prepared by solution casting, turned out to improve the crystallinity of the polymer. Moreover, IR measurements dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
(86 reference statements)
0
24
0
Order By: Relevance
“…As polymer matrix, polylactic acid (PLA) was exploited, being a biocompatible synthetic polymer widely used as drug support and in various other biomedical applications. 18,19 In particular, stereocomplex PLA (sc-PLA), which is produced by the combination of the enantiomeric PLLA and PDLA, was taken into account because of the higher thermal and hydrolysis resistance with respect to either mere PLLA or PDLA. 20,21 On this respect, it is worth underling that, for the envisaged applications, the polymer matrix should be biodegradable but not easily decomposed by the carried enzymes.…”
mentioning
confidence: 99%
“…As polymer matrix, polylactic acid (PLA) was exploited, being a biocompatible synthetic polymer widely used as drug support and in various other biomedical applications. 18,19 In particular, stereocomplex PLA (sc-PLA), which is produced by the combination of the enantiomeric PLLA and PDLA, was taken into account because of the higher thermal and hydrolysis resistance with respect to either mere PLLA or PDLA. 20,21 On this respect, it is worth underling that, for the envisaged applications, the polymer matrix should be biodegradable but not easily decomposed by the carried enzymes.…”
mentioning
confidence: 99%
“…This system allows combined cell targeted chemotherapy and immunotherapy; this coordination assembly displayed therapeutic advantage when tested in a human carcinoma [75]. Furthermore, Gardella et al [76] reported a drug delivery system based on a porphyrin, poly(L-lactide), and graphite; this material proved extremely promising in drug delivery filed.…”
Section: Porphyrins and Metalloporphyrins For Drug Deliverymentioning
confidence: 99%
“…It was first obtained from graphite by Geim and Novoselov in 2004, and it has excellent electrical conductivity and thermal properties, unique microstructure and unique optical properties, good biocompatibility, and good mechanical properties . Given such outstanding properties, methods for synthesis of graphene have been expanded upon and improved continuously ,. As a consequence, applications of graphene in biomedicine have also been increasing.…”
Section: Structure and Properties Of Graphene‐family Materialsmentioning
confidence: 99%